PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT UMUM KASIH BUNDA KOTA CIMAHI - Iska Ayu Saparina; Budi Prasetiyo (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This research was conducted on inpatients at Kasih Bunda Cimahi General Hospital. This study aims to determine how much influence quality and facilities had on inpatient satisfaction either partially or simultaneously in inpatients at Kasih Bunda Cimahi General Hospital. This study uses a descriptive and associative methodology with a quantitative approach. Inpatients in the Arjuna, Nakula, Shinta, and Bima rooms became the unit of analysis for this study. The sample for this study consisted of ninety respondents. By using stratified random sampling, this study used a systematic random sampling method. In addition to verifying the validity and reliability of research tools, the analytical approach uses multiple linear regression analysis. According to research findings, service quality has a partial effect of 12.01% on inpatient satisfaction, while facilities have a partial effect of 19.01%. Nevertheless, the total effect is only 31%. To further increase customer satisfaction, the hospital will provide outreach to all divisions related to hospital services.